2006
DOI: 10.1080/08880010600751918
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hfe Mutations in California Newborns

Abstract: Advances in molecular diagnostics have led to an increased interest in expanding population-based screening to include genetic diseases that occur outside the newborn period. Hereditary hemochromatosis may be a candidate for large-scale screening in populations with a high prevalence of the common HFE mutations. To determine race-specific frequencies of the HFE mutations, C282Y and H63D, the authors applied an automated, high-throughput genotyping method to dried blood spot samples from a representative popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
(66 reference statements)
0
5
0
Order By: Relevance
“… 48 Subsequent case–control studies have reported a median p.C282Y/p.H63D compound heterozygous genotype frequency among clinically characterized hemochromatosis cohorts of 4.6% (0–21.7%), 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 which is significantly higher than the compound heterozygote frequency of 1.7% (0–7.7%) reported in screening studies. 60 , 63 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 ,...…”
Section: Methodology and Resultsmentioning
confidence: 99%
“… 48 Subsequent case–control studies have reported a median p.C282Y/p.H63D compound heterozygous genotype frequency among clinically characterized hemochromatosis cohorts of 4.6% (0–21.7%), 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 which is significantly higher than the compound heterozygote frequency of 1.7% (0–7.7%) reported in screening studies. 60 , 63 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 ,...…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…In 2002, DNA was extracted from punches from 4000 blood cards using QiaAmp 96 DNA Blood kits (Qiagen, Valencia, CA) in a 96-well block extractor per manufacturers instructions[3]. Cards were not sorted by ethnicity prior to DNA preparation; thus, African American samples were distributed at random among the total sample set[4].…”
Section: Methodsmentioning
confidence: 99%
“…Advanced read-out Mass spectrometry based, capillary electrophoresis, chip based n/a n/a n/a + [174][175][176][177][178][179] Reverse hybridization assay Multiplex PCR amplification followed by reverse hybridization n/a n/a n/a + [21,150,180,181] Novel extraction methods Dried blood spots, whole-blood PCR n/a n/a n/a ++ [38,158,182] Whether they are screened with the above procedure depends upon their age, health status, and the attitude of the family.…”
Section: Family Screeningmentioning
confidence: 99%